PAI Learning Transformation in the Digital Era: Implementation of Innovative Digital Media - Hanim, Madhurika; Hafidz, Hafidz (Institut Agama Islam An-Nawawi Purworejo, 2025)
This research aims to explore the creativity of Islamic Religious Education (PAI) teachers in using digital learning media as an innovative effort to overcome learning boredom for students in grades 7-8 at SMP Muhammadiyah 1 Kartasura. This research uses a qualitative approach with a case study method through interviews, observation and documentation. The research results show that media such as smart TV, the Quizizz application, and Microsoft Word are effective in increasing student participation and understanding. Supporting factors for success include adequate school facilities and teacher openness to technology. However, challenges such as a lack of variety in learning methods are still faced. This research underlines the importance of innovation in technology-based learning to create interesting and relevant learning experiences.